2012
DOI: 10.1200/jco.2012.41.8137
|View full text |Cite|
|
Sign up to set email alerts
|

Stage-Adapted Treatment of HIV-Associated Hodgkin Lymphoma: Results of a Prospective Multicenter Study

Abstract: In patients with HIV-HL, stage- and risk-adapted treatment is feasible and effective. The prognosis for patients with HIV-HL may approach that of HIV-negative patients with HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 26 publications
4
64
4
6
Order By: Relevance
“…However, current data from prospective and retrospective trials have shown promising results. In the prospective German multicenter study using a stage-adapted treatment approach, CR rates were 96% for early-stage favorable, 100% for early-stage unfavorable, and 86% for advanced-stage HL [54]. 2 comparative studies on ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) in HL showed that HIV infection did not adversely affect progression-free and event-free survival or OS [41,55].…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, current data from prospective and retrospective trials have shown promising results. In the prospective German multicenter study using a stage-adapted treatment approach, CR rates were 96% for early-stage favorable, 100% for early-stage unfavorable, and 86% for advanced-stage HL [54]. 2 comparative studies on ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) in HL showed that HIV infection did not adversely affect progression-free and event-free survival or OS [41,55].…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%
“…Patients with early favorable disease should receive 2 cycles of ABVD with subsequent 20-Gy involved-field radiotherapy. 4 cycles of ABVD followed by 30-Gy involved-field radiotherapy is the treatment of choice for patients with early unfavorable disease, and patients with advanced stage should receive 6 cycles of BEA-COPP baseline (bleomycin, etoposide, adriamycin, cyclophosphamide, vincristine, procarbazine, prednisolone) or 6-8 cycles of ABVD [54].…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%
“…Several clinical trials (17)(18)(19)(20)(21) and observational studies (22)(23)(24) with HIV-infected lymphoma cases treated with HAART reported survival outcomes comparable to general patients with lymphoma. However, a few studies directly compared HIV-infected and HIV-uninfected patients with lymphoma and found inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…The 2-year overall survival (OS) rate in the entire cohort was 90.7%. 62 However, BEACCOPP was toxic; dose reductions and delays were common, and treatment-related mortality was 7%. Our approach is to avoid BEACOPP in HIV-cHL, with the possible exception of responseadapted therapeutic escalation.…”
Section: Primary Chemotherapy For Hiv-chlmentioning
confidence: 99%